Using standardized assessment to identify and teach prerequisite numeracy skills to learners with disabilities using video modeling. Issue 5 (26th December 2020) - Dueker, Scott A.; Day, Jayda M.
Abstract: Learners with disabilities enter school without the prerequisite numeracy and mathematics skills to perform at or near the level of their typically developing peers. Even simple addition problems require prerequisite skills that are often not taught directly in schools. Identifying and teaching those missing skills would reduce the learning gap and increase the lifelong independence of those learners. This study used a nonconcurrent single‐subject multiple baseline design across five learners with a pretest/posttest analysis to examine the use of a norm‐referenced, standardized assessment to identify gaps in student learning, create teaching protocols using video modeling, and assess overall growth after intervention. Individualized interventions were delivered using video models on iPads. Results indicated all learners were able to use the video models to acquire the missing skills and improve overall mathematics understanding, as measured by scores on a posttest. This has classroom implications due to the relative ease of administration of the assessment and teaching protocol as well as the potential for improved outcomes for the learners.